124k views
4 votes
-2x-+5x-9
3x-13
simplify the expression

2 Answers

6 votes

Answer:

(-7x-9)+(3x-13)= -4x-22

Simplify the first one -2x-(5x)-9= -7x-9

Put the thing together that fit (Add the terms together)

:)Hope you enjoy this:)

User Paul Gowder
by
6.8k points
3 votes

Answer:

(-2x)-5x-9 = (-7x)-9

3x - 13 = 3x - 13 (you cannot simplify more)

Your question was wery wierd but i tried to answer best I could.

And also I dont know what you mean about "-+5"

User Louis Ingenthron
by
4.7k points